Melia azedarach L. extracts and their activity on Musca domestica L. (Diptera: Muscidae) - Cabral,Marise M. O. (2008)
Crudes extracts and fractions from seeds of Melia azedarach L. (Meliaceae) have been assayed on Musca domestica Linnaeus, 1758 (Diptera: Muscidae). Thus, the post-embryonic development of the flies was reduced and the delay from newly hatched larvae to adults had significant increase. In addition, the pupal weights were reduced and the sexual ratio altered. Toxicity to fly eggs was also observed.